Button Gastrostomy Tubes for Pediatric Patients: A Tertiary Care Center Experience - Fayza Haider; Hasan Mohamed Ali Isa; Mohamed Amin Al Awadhi; Barrak Ayoub; Ezat Bakhsh; Husain Al Aradi; Shahraban Abdulla Juma (International Journal of Pediatrics)
Background and Objective. Gastrostomy tube insertion is one of the most common procedures performed as a radical choice to overcome feeding difficulty in children. This study is aimed at describing the replacement of a button tube instead of the long tube for feeding infants and children requiring gastrostomies in a tertiary care hospital. Design and Setting. This retrospective cross-sectional descriptive study was conducted between January 2009 and August 2019 at Salmaniya Medical Complex which is a tertiary health care institute in the Kingdom of Bahrain. Subjects and Methods. Both charts and electronic health records of pediatric patients between the ages of 0 and 14 years were reviewed. Data were collected including age, sex, nationality, diagnosis, surgical information (procedure center and procedure performed), complications, and follow-up. Results. Out of 34 patients who underwent gastrostomy tube insertion, 30 patients had their long tube replaced by a button gastrostomy. Majority were males (N=18, 60%). Prolonged nasogastric tube feeding was the main indication of referral (N=17, 56%) followed by feed intolerance (N=6, 17%) and gastroesophageal reflux disease (N=5, 16%). The main underlying diseases at referral were neurological impairment (N=19, 63%) and metabolic disorders (N=4, 13%). There was no significant difference between patients with neurological disorders and other diseases in terms of gender, nationality, or age. Laparotomy with gastrostomy is the main approach used (N=18, 60%). No reported complications of button tubes in 50% of the patients (N=15). Conclusions. Prolonged nasogastric tube feeding is the main indication of referral for gastrostomy tube insertion. Neurological disorders are the main diagnosis for the cases operated upon. Laparotomy with gastrostomy is the procedure of choice at our center. Majority of patients had no reported complications of button tube replacement. These children are likely to benefit from the button tube with fewer complications.